2021
DOI: 10.3390/cells10020423
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-27b-3p Targets the Myostatin Gene to Regulate Myoblast Proliferation and Is Involved in Myoblast Differentiation

Abstract: microRNAs play an important role in the growth and development of chicken embryos, including the regulation of skeletal muscle genesis, myoblast proliferation, differentiation, and apoptosis. Our previous RNA-seq studies showed that microRNA-27b-3p (miR-27b-3p) might play an important role in regulating the proliferation and differentiation of chicken primary myoblasts (CPMs). However, the mechanism of miR-27b-3p regulating the proliferation and differentiation of CPMs is still unclear. In this study, the resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…For each circRNA, the target miRNAs with the highest score were selected from 95 target miRNAs and then used to construct a circRNA-miRNA network (Figure 6). Some miRNAs that have been previously reported to be associated with the growth and development of skeletal muscle and the proliferation and differentiation of preadipocytes were found, including miR-140-3p, miR-129-5p, miR-424-5p, miR-27b-3p and miR-30a-3p [6, [37][38][39][40].…”
Section: Functional Analysis Of Circrnas As Mirna Spongesmentioning
confidence: 99%
“…For each circRNA, the target miRNAs with the highest score were selected from 95 target miRNAs and then used to construct a circRNA-miRNA network (Figure 6). Some miRNAs that have been previously reported to be associated with the growth and development of skeletal muscle and the proliferation and differentiation of preadipocytes were found, including miR-140-3p, miR-129-5p, miR-424-5p, miR-27b-3p and miR-30a-3p [6, [37][38][39][40].…”
Section: Functional Analysis Of Circrnas As Mirna Spongesmentioning
confidence: 99%
“…MiR-21-5p targets KLF3 and regulates skeletal muscle satellite cell proliferation and differentiation [ 32 ]. MicroR-27b-3p regulates the proliferation and differentiation of chicken primary myoblasts by targeting MSTN [ 33 ]. Moreover, miRNA-214 regulates chicken myoblast proliferation and differentiation by targeting TRMT61A [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, whether our research object miR-27b-3p can affect muscle atrophy through miR-27b-3p/PPARγ/ATGL pathway remains to be further studied. In chickens, miR-27b-3p significantly promoted the proliferation of chicken primary myoblasts (CPMs) by targeting myostatin (MSTN) and inhibited the differentiation of CPMs [ 39 ]. Interestingly, some studies have shown that in mice, excessive retinoic acid upregulates miR-27b-3p and targets α-dystrobrevin to inhibit myoblast proliferation and differentiation [ 40 ].…”
Section: Discussionmentioning
confidence: 99%